Peningkatan Hasil Belajar dengan Problem Best Learning dalam Memahami Struktur Teks dan Unsur Kebahasaan dalam Nulis Layang Pribadhi - Dami, Dami (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Students' achievements in learning to understand text structure and linguistic elements in personal writing are still not satisfactory. This is because the teacher is not correct in choosing learning methods. The basic problem in this research is that the majority of students in class VIII C of SMP Negeri 9 Surabaya for the 2021/2022 academic year are less capable in writing layang pribadhi. The aim of this research is to determine the increase in learning achievement with problem based learning in understanding text structure and linguistic elements in writing layang pribadhi. This research uses action research because it is more in line with the main duties and functions of teachers to improve the quality of learning, the quality of students, and achieve learning or educational goals. The research subjects were 38 students in class VIII C of SMP Negeri 9 Surabaya for the 2021/2022 academic year. This research was conducted in February 2022. The data collection methods in this research were observation, tests, and field notes with data analysis techniques used in data reduction, data presentation, drawing conclusions, and reflection verification. The research results showed that the average value of learning outcomes before the action was 68.26, in the first cycle it was 76.81 while in the second cycle it was 90.05. Before the action, there were 7 (18.42%) students who had completed their studies, in Cycle I there were 23 (61.54%) students who had completed their studies, while in Cycle II there were 35 (91.10%) students who had completed their studies. Before the action, the quality of learning was 68.26, while in cycle I it was 76.81 and in Cycle II it was 90.05. With an increase in learning outcomes, it can be concluded that problem based learning can be used to improve student learning achievement in understanding text structure and linguistic elements in layang pribadhi writing. Keywords : problem based learning, learning outcomes, text structure and linguistic elements